Current State and Problems of Treatment of Postoperative Ventral Hernias in Women of Reproductive Age - Khamdamov I. B (Periodica Journal, 2022)
The essence of the experiment was to conduct research on tissue rupture. Taking into account the fact of different extensibility of tissues in different parts of the anterior abdominal wall during pregnancy, we studied the initial morphological characteristics of the tissues of the anterior abdominal wall and the nature of the changes during its maximum stretching
Keywords: maximum; anterior; research; nature